Neighborhood Characteristics as Predictors of Male to Female and Female to Male Partner Violence - Caetano, Raul (2009)
This article examines the association between neighborhood characteristics at the census tract–level, couples’ perceived neighborhood social cohesion and informal social control, and male-to-female (MFPV) and female-to-male (FMPV) partner violence in the United States. Data come from a second wave of interviews (2000) with a national sample of couples 18 years of age and older who were first interviewed in 1995. The path analysis shows that poverty is associated with perceived social cohesion and perceived social control as hypothesized. However, there is no significant mediation effect for social control or social cohesion on any type of violence. In the path analysis, Black ethnicity is associated with social cohesion, which is associated with MFPV. Intimate partner violence (IPV), as a form of domestic violence, may not be as concentrated in high-poverty neighborhoods as criminal violence. IPV may be more determined by personal and dyadic characteristics than criminal violence.